(untitled) (Third Sector Social Economic Review, 2023)
One of the macroeconomic problems that developed and developing countries are trying to solve is unemployment. Unemployment, which is defined as the inability of people who want to work to find a job, also indicates low economic efficiency. In this context, the unemployment rate gives us the opportunity to have information about the economic development level of the countries, while the high unemployment rate can pave the way for a low level of economic development. Recent developments in the national and international arena have created changes in unemployment rates. The environment created by the debt crisis, which affected many European countries together with the developments in the USA in 2007 and later turned into a global crisis, affected the dynamics in the labor market. While the disruption of production and supply chains caused by the Covid-19 epidemic resulted in people losing their current jobs, disruptions in global economic activities caused serious recession. In this study, the effects of per capita income, foreign trade and human capital on the unemployment rate in the Turkish economy were investigated by using the Fourier ARDL cointegration method for the period 1970-2019. According to the results of the Fourier ARDL cointegration test performed to determine the long-term relationship between the variables, no statistically significant cointegration relationship was found between the variables. Therefore, no findings on the effects of per capita income, foreign trade and human capital on unemployment could be reached for Turkey.